TSRP: A Trust based Secure Routing Protocol for Authentication and Load balancing in MANET - Prof. S. Madhumitha, Dr. N. A. Natraj, Dr. S. Gopinath, Dr. N. Suresh Kumar (International Journal of Advanced Science and Technology, 2020)
Ad Hoc Networks plays a vital role of wireless networks. Security is a major issue of Mobile Ad hoc Network (MANET). Due to the absence of access point, information may be compromised by means of attackers. It is concluded from the existing survey, the security approaches are lagging to satisfy the attackers. In this research work, the Trust based Security Protocol (TSRP) is proposed to provide balanced routing and authentication among the nodes. In first phase, load balanced routing is established to achieve less packet loss rate. In second phase, trust based security approach is developed to attain reliability. Each node carries trust value and packet contains trust ID to avoid misbehavior. The security is attained through asymmetry key cryptography. The performance of TSRP is evaluated in terms of authentication rate, throughput, packet reliability rate and propagation delay.